Análise de políticas tarifárias do transporte público do município de Belo Horizonte sob a ótica da elasticidade demanda-tarifa - Sérgio Luís Ribeiro de Carvalho (2012)
This dissertation aims to evaluate the various changes in pricing policy that have occurred in the last decade in the public bus passenger transport system in the city of Belo Horizonte from the perspective of price demand elasticity. The demand variations have occurred due to the implementation of fare changes related to actions implemented in the public transport system in the regions of the Barreiro District, Venda Nova and Sao Gabriel; the reduction of bus fare when traveling on the second trip inside the integrated service; the integration between the regular lines and of villages and slum quarter lines; the integration between lines operating in the central area; and, finally, the fare policies for Sundays and holidays. The price elasticity has been estimated for each policy implemented. The findings have confirmed that the demand for urban public transport is sensitive to fare variations and that public policies undertaken to reduce fare levels may be combined with service improvements, without necessarily resulting in reduced revenue.